2010
DOI: 10.1161/strokeaha.109.577288
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment With VELCADE and Low-Dose Tissue Plasminogen Activator Provides Potent Neuroprotection in Aged Rats After Embolic Focal Ischemia

Abstract: Background and Purpose Treatment with a selective proteasome inhibitor, VELCADE, in combination with tissue plasminogen activator (tPA) extended the therapeutic window to 6 hours in young rats after stroke. However, stroke is a major cause of death and disability in the elderly. The present study investigated the effect of VELCADE in combination with a low-dose tPA on aged rats after embolic stroke. Methods Male Wistar rats at the age of 18 to 20 months were treated with VELCADE (0.2 mg/kg) alone, a low-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…23,24 Given that KLF2 is known to confer potent anti-inflammatory effects and induce eNOS, it is possible that these observations are secondary to increased KLF2 levels, as suggested by our studies.…”
Section: Klf2 Alters the Expression Of Thrombotic Targetsmentioning
confidence: 74%
“…23,24 Given that KLF2 is known to confer potent anti-inflammatory effects and induce eNOS, it is possible that these observations are secondary to increased KLF2 levels, as suggested by our studies.…”
Section: Klf2 Alters the Expression Of Thrombotic Targetsmentioning
confidence: 74%
“…Furthermore, when combined with tissue plasminogen activator (tPA), MLN519 reduced the infarct volume and improved the neurological outcome as determined 1 week after stroke . Similarly, the proteasome inhibitor bortezomib combined with low doses of tPA showed additional neuroprotective effects when tested in a model of embolic stroke in rats (Zhang et al, 2006b(Zhang et al, , 2010. Single administration of bortezomib within 2-4 h after injury also showed neuroprotective effects, and the proteasome inhibitor was proposed to act by promoting eNOSdependent vascular protection and to prevent NF-kB-dependent vascular disruption (Zhang et al, 2006b(Zhang et al, ,c, 2010.…”
Section: Protective Effects Of Proteasome Modulators In Brain Ischemiamentioning
confidence: 99%
“…10,11 In contrast to our present results, other studies have reported beneficial effects of certain proteasome inhibitors when given as monotherapy during brain ischemia/reperfusion injury. 38,39 The exact reasons for this discrepancy are unclear at present. Differences in stroke models (eg, embolic stroke versus filament occlusion of the middle cerebral artery) and animal species (rat versus mouse) as well as divergent proteasome inhibitor formulations might play a role here.…”
mentioning
confidence: 96%